(untitled) (Physical Education, Health and Social Sciences, 2025)
In this study, analysis of the language shift of Punjabi speakers in Sargodha has been carried out by examining the effects of attitudes, education, media exposure and migration. The mixed-method design was applied and included quantitative surveys with qualitative semi-structured interviews. The respondents were 150 in number and the analysis of the data shows that Punjabi is largely used in non-formal spheres of life, including home and community life, yet its application is reducing in educational, work, and online life. There are favorable cultural attitudes towards Punjabi, but realistic factors, prestige attached to Urdu and English, media content exposure, and migration will play a huge role in determining language preference. Qualitative analysis of data through thematic analysis identifies intergenerational language change, media impact, institutional discrimination in education, and internalized negative attitudes as major drivers of the Punjabi degradation. Another method to corpus that was used was quantitative analysis with the help of the AntConc software to extract frequency patterns, collocations, and keyword trends of interview transcripts, and presented numerical corpus evidence to back up the qualitative results.. The paper concludes with the finding that although the Punjabi lingo still has a symbolic and cultural significance, the functional areas are becoming smaller, especially among the younger speakers. The study highlights the fact that educational changes, media advertisement, community-based as well as policy-based interventions are needed to help maintain and revive Punjabi in Sargodha. Future research recommendations involve investigating the impact of urbanization, longitudinal changes, and gender variation in language preservation.